2017
DOI: 10.7717/peerj.3796
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of cultivated aerobic poly-hydrolytic bacteria in saline alkaline soils

Abstract: Alkaline saline soils, known also as “soda solonchaks”, represent a natural soda habitat which differs from soda lake sediments by higher aeration and lower humidity. The microbiology of soda soils, in contrast to the more intensively studied soda lakes, remains poorly explored. In this work we investigate the diversity of culturable aerobic haloalkalitolerant bacteria with various hydrolytic activities from soda soils at different locations in Central Asia, Africa, and North America. In total, 179 pure cultur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…In addition to S. aureus, another two Gram-positive organisms were tested as substrate for AB-CW3 -Micrococcus luteus (DSM 20030) and the haloalkaliphilic actinobacterium Isoptericola sp. DS111 (Sorokin et al, 2017b). Isoptericola grows as a suspension of individual cells.…”
Section: Microbial Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to S. aureus, another two Gram-positive organisms were tested as substrate for AB-CW3 -Micrococcus luteus (DSM 20030) and the haloalkaliphilic actinobacterium Isoptericola sp. DS111 (Sorokin et al, 2017b). Isoptericola grows as a suspension of individual cells.…”
Section: Microbial Physiologymentioning
confidence: 99%
“…To investigate whether it was also able to grow with other Gram-positive bacteria, AB-CW3 was incubated with cells of Micrococcus and Isoptericola. The latter is a halo-alkaliphilic Actinobacterium isolated from a saline soda soil in the same area as AB-CW3 (Sorokin et al, 2017b). Both Micrococcus and Isoptericola supported growth of AB-CW3.…”
Section: Substrates and Growth Conditions Of Ab-cw3mentioning
confidence: 99%
“…Several studies have suggested two main reasons for the decrease in net photosynthetic rate under saline-alkaline stress, namely stomatal restriction caused by partial closure of stomata and decreased cell viability [34][35][36]. The decrease in intercellular carbon dioxide concentration and stomatal conductance were the main reasons for the decreased photosynthesis rates [37].…”
Section: Effects Of Salt Stress On Photosynthesismentioning
confidence: 99%